Bacterial and Yeast Endophytes from Poplar and Willow Promote Growth in Crop Plants and Grasses. (15th October 2012) - Khan, Zareen; Guelich, Grant; Phan, Ha; Redman, Regina; Doty, Sharon
Abstract : Endophytic associations with plants have a beneficial effect for many different plant species with some of them being host specific. Several endophytes isolated from poplar and willow were screened for their effects on commercially important crops including corn, tomato, pepper, squash, sunflower, and grasses. Most of these endophytes produce growth hormones such as indoleacetic acid (IAA) and have the nitrogenase gene required for nitrogen fixation. The effects of these isolates on plant growth and yield were evaluated under greenhouse conditions. We found that inoculated plants not only had better viability and earlier flowering and fruiting, they also had increased plant growth and fruit yields when grown in nitrogen-limited soil. In a particular variety of perennial rye grass, the endophytes increased the total nitrogen content of the plants, indicative of nitrogen fixation, in addition to promoting plant growth. The use of specific endophytes may be preferable to the use of chemical fertilizers because of the monetary and environmental costs, contributing to more sustainable agricultural systems.